Clericuzio‐type poikiloderma with neutropenia in a patient from India. Issue 1 (27th October 2020) - Bishnoi, Anuradha; Jamwal, Manu; Das, Reena; Scaria, Vinod; Vishwajeet, Vikarn; De, Dipankar; Saikia, Uma Nahar; Mahajan, Rahul
Abstract: A 9‐year‐old boy presented for evaluation of variegated skin pigmentation. Palms and soles revealed honeycombed hyperpigmented hyperkeratosis. Irregular, firm, skin coloured nodules suggestive of cutaneous calcification were present on both elbows. Total leucocyte count and absolute neutrophil count were 3720/mm3 and 420/mm3 respectively. The neutropenia was not cyclical. Systematic analysis of the whole exome data revealed a homozygous mutation in USB1 gene; chr16:g.58043892TA>‐[1/1]. A final diagnosis of poikiloderma with neutropenia‐ Clericuzio type (PNC) was made. Naegeli Franceschetti Jadassohn, dermatopathia pigmentosa reticularis, PNC and dyskeratosis congenita, all can present with overlapping cutaneous manifestations. Subtle clinical details like thickened nails, hyperextensible joints, calcinosis cutis, characteristic facies and a preceding erythematopapular rash strongly favor the diagnosis of PNC. The index case highlights two novel findings: obliterated dermatoglyphics and mucin deposition (features not described hitherto in PNC).